2010
DOI: 10.1073/pnas.1001075107
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the planar cell polarity formin DAAM1 leads to inhibition of endothelial cell proliferation, migration, and angiogenesis

Abstract: The Wnt/planar cell polarity (PCP) pathway regulates directed cell movement during development and was recently found to play a critical role in endothelial cell proliferation and angiogenesis [Zhang Y, et al. (2006) Chem Biol 13:1001-1009 Masckauchan TN, et al. (2006) Mol Biol Cell 17:5163-5172]. However, the mechanisms by which PCP signaling components regulate angiogenesis remain unknown. We report that expression of a constitutively active Cterminal domain of Dishevelled-associated activator of morphogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 39 publications
(46 reference statements)
2
60
0
Order By: Relevance
“…25 As a next step, hCMEC/D3 cells were treated during 6 days with Wnt5a (40% conditioned medium of Wnt5a producing LM (TK) cells (ATCC #CRL-2814), as previously described. 26 As control, lithium chloride 10 mmol/L was used as an activator of the Wnt/b-catenin canonical pathway: indeed, we observed that hCMEC/D3 cells were treated with control small interfering RNA (si CTR) or two distinct siRNAs against PAR-3 (#A, #B).…”
Section: Wnt5a Regulation Of Hcmec/d3 Permeability Is Mediated By Thementioning
confidence: 99%
“…25 As a next step, hCMEC/D3 cells were treated during 6 days with Wnt5a (40% conditioned medium of Wnt5a producing LM (TK) cells (ATCC #CRL-2814), as previously described. 26 As control, lithium chloride 10 mmol/L was used as an activator of the Wnt/b-catenin canonical pathway: indeed, we observed that hCMEC/D3 cells were treated with control small interfering RNA (si CTR) or two distinct siRNAs against PAR-3 (#A, #B).…”
Section: Wnt5a Regulation Of Hcmec/d3 Permeability Is Mediated By Thementioning
confidence: 99%
“…The Wnt/PCP pathway also appears to play a role in angiogenesis, particularly vascular morphogenesis and endothelial cell proliferation (44). Recently, the formin Dvl-associated activator of morphogenesis-1, an essential player in cytoskeletal organization, was found to be a downstream intermediate of the Wnt/PCP pathway in regulating endothelial cell proliferation and angiogenesis (45). It has been recently demonstrated that Fz-4 acts in arterial formation and organization through a Wnt/ PCP pathway, altering Golgi organization and tubulin acetylation (46).…”
Section: Noncanonical Wnt Signaling In Angiogenesismentioning
confidence: 99%
“…Although the roles and molecular interactions of PCP proteins in fly epithelia have been studied in some detail (Bastock et al, 2003;Jenny et al, 2005;Tree et al, 2002b;Wu and Mlodzik, 2008), accumulating evidence indicates that vertebrate PCP components have functions that are not directly related to cell polarity in the plane of the tissue. Vertebrate PCP proteins are now known to control a large number of developmental processes, including inner ear polarity (Montcouquiol et al, 2003), left-right patterning (Antic et al, 2010;Borovina et al, 2010;Hashimoto et al, 2010;Song et al, 2010), mesodermal convergent extension (Keller, 2002;Sokol, 2000), neural tube closure (Copp and Greene, 2010;Sokol, 1996), neurite extension, neuronal migration, branching morphogenesis and vascular development (Carroll and Yu, 2012;Gray et al, 2011;Jessen et al, 2002;Ju et al, 2010;Tissir and Goffinet, 2013;Yates et al, 2010b). The molecular mechanisms underlying this pleiotropic behavior of PCP proteins in morphogenesis remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%